USM WELCOMES COURTESY VISIT FROM THAILAND HIGHER EDUCATION PLANNING NETWORK - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 13 May 2016 – Universiti Sains Malaysia (USM) received a courtesy visit from a group comprising of 95 officials and academic staff from the Higher Education Planning Network Thailand recently.